INTEGRATED BIOLOGICAL AND CHEMICAL TREATMENT OF BREWERY SLUDGE (Biological Sciences - PJSIR, 2004)
Composite samples of sludges obtained from a brewery in Benin City were analysed for their pollution characteristics. The samples were then treated by integrated biological and chemical methods. The analysis revealed that the BOD and COD of the sludge liquor were high, as well as the levels of solids concentration, nitrogen, phosphorus and total bacterial counts. These showed that sludge from the brewery have high pollution potentials and therefore, needed treatment before disposal or reuse. The sludges were treated by integrated biological and chemical methods. Percentage solids reduction achieved were in the range of 21.4 - 27% total solid (TS), 27 - 32% suspended solids (SS) and 32 - 48% volatile solids (VS) for integrated aerobic/chemical treatment and 24.3 - 27.2% TS, 30.3 - 33% SS and 34.4 - 36% VS for anaerobic/ chemical treatment. BOD and COD reductions were in the range of 97 - 98 and 97.3 - 98.2%, respectively for aerobic/ chemical treatment and 97.7 - 97.9 and 98 - 98.3%, respectively for anaerobic/chemical treatment. Phosphorus, ammonia and nitrate nitrogen were found to be substantially reduced in this sludge thus preventing the eutrophication of water bodies, up to 57 - 85.2% NH3 and 31.7 - 61.9% NO3. Reduction was achieved using aerobic/chemical treatment while the anaerobic/chemical method achieved a reduction of up 100% NO3 .